Galangin Regulates Astrocyte Phenotypes to Ameliorate Cerebral Ischemia-reperfusion Injury by Inhibiting the RhoA/ROCK/LIMK Pathway - Liu, Nannuan; Xu, Yue; Liu, Yao; Chen, Tao; Hu, Wenli (Current Pharmaceutical Design, 2025)
PurposeThis study aimed to explore whether Galangin (Gal) could improve cerebral Ischemia- reperfusion (I/R) injury by regulating astrocytes, and clarify its potential molecular mechanism.MethodsAn I/R injury model of rats was established using the Middle Cerebral Artery Occlusion/Reperfusion (MCAO/R) method, followed by the administration of Gal (25, 50, 100 mg/kg) via gavage for 14 consecutive days. Besides, astrocytes were isolated from the rats to construct an Oxygen-Glucose Deprivation/Re-oxygenation (OGD/R) cell model, with treatments of Gal or the Ras homolog gene family member A (RhoA)/Rho-associated Coiled-coil containing protein Kinase (ROCK) inhibitor Y-27632. Subsequently, the severity of nerve injury was assessed using the modified Neurological Severity Score (mNSS) test; behavioral disorders in I/R rats were observed through the open field and ladder-climbing tests. Pathological damages and neuron survival in the peri-infarct zone were examined by hematoxylin and eosin staining and NeuN staining, respectively. Additionally, immunofluorescence staining was employed to determine astrocyte polarization and TUNEL staining was carried out to measure the level of cell apoptosis; also, western blot was performed to detect the expression of proteins related to the RhoA/ROCK/LIM domain Kinase (LIMK) pathway.ResultsGal significantly ameliorated the neurological and motor dysfunctions caused by I/R in rats, reduced pathological damage in the peri-infarct zone, and promoted neuronal survival. Additionally, Gal increased the number of A2 astrocytes, while it decreased the number of A1 astrocytes. In vitro experiments revealed that the effect of Gal was consistent with that of Y-27632. Additionally, Gal significantly enhanced the survival of OGD/R cells, increased the number of A2 astrocytes, and inhibited the expression of proteins associated with the RhoA/ROCK pathway.ConclusionGal could reduce the level of apoptosis, promote the polarization of A2 astrocytes, and improve cerebral I/R injury, and its mechanism may be related to the inhibition of the RhoA/ROCK pathway.
Keywords: polarization